2015
DOI: 10.3109/01676830.2015.1049370
|View full text |Cite
|
Sign up to set email alerts
|

P63 Positive Mucoepidermoid Tumor of the Lacrimal Sac with Associated Papilloma

Abstract: We report a case of a 44-year-old man who presented with a left medial canthal mass and epiphora. Imaging was suggestive of a mass continuous with the nasolacrimal sac. Subsequent surgical exploration revealed a mass adherent to bone with invasion of the lacrimal system. Histological examination revealed a squamous/transitional cell papilloma overlying a low-grade mucoepidermoid carcinoma (MEC). Complete surgical resection was completed and pathology confirmed the diagnosis. This is the first case in which a M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Common benign epithelial neoplasms include squamous cell papilloma and transitional cell papilloma. Benign nonepithelial tumors are fibrous histiocytomas [23, 29-35, 37]. The others include epithelial oncocytoma and a benign mixed tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Common benign epithelial neoplasms include squamous cell papilloma and transitional cell papilloma. Benign nonepithelial tumors are fibrous histiocytomas [23, 29-35, 37]. The others include epithelial oncocytoma and a benign mixed tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Open biopsy was the preferred biopsy technique rather than FNAB in this study. Incisional biopsy is helpful for suspicious lacrimal sac tumors [22, 36, 37, 42-44, 46, 47]. Immunohistochemical analysis is important to confirm malignant cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 ] A previous publication demonstrated that mucoepidermoid carcinoma of lacrimal gland could be strongly stained with p63. [ 13 ] Based on the morphology of tumor tissue and clinical signs of patients, mucoepidermoid could be ruled out. CEPA is considered to be a type of carcinoma that exhibits histological features of benign pleomorphic adenoma.…”
Section: Discussionmentioning
confidence: 99%